Human T-Lymphotropic Virus-1–Associated Myelopathy/Tropical Spastic Paraparesis Is Associated With Sexual Dysfunction in Infected Women of Reproductive Age. Issue 4 (1st September 2018) - Lopes Martins, Adenilda Lima; Rios Grassi, Maria Fernanda; de Aquino Firmino, Alisson; Lacerda Araujo, Jean Paulo; Paixao, Taiane Silva; Galvão-Castro, Bernardo; Boa-Sorte, Ney
Abstract: Introduction: Human T-lymphotropic virus (HTLV)-1–associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a neurological disorder that mostly affects women. This disease is characterized by a progressive loss of motor function and disruptions in sensory function in the lower limbs. HTLV-1 is also associated with isolated neurologic dysfunctions, overactive bladder, and erectile dysfunction. The occurrence of sexual dysfunction in HTLV-1–infected women remain unclear. Aim: To investigate associations between HTLV-1 infection and sexual dysfunction in both asymptomatic infected women and those diagnosed with HAM/TSP compared with uninfected women. Methods: HTLV-1–infected and uninfected women were assessed for sexual dysfunction using the Female Sexual Function Index instrument. Sexual dysfunction was considered if global Female Sexual Function Index scores were <26.5. Crude and adjusted prevalence ratios (PR) with 95% CI were calculated to identify associations between sexual dysfunction (outcome) and HTLV infection status–asymptomatic or HAM/TSP (main exposure), compared with uninfected women, and adjusted by sociodemographic and/or clinical characteristics (covariables). Results: HTLV-1–infected women (n = 72; 57 asymptomatic; 15 HAM/TSP) and HTLV-1 uninfected women (n = 49) were evaluated. The overall sexual dysfunction prevalence was 53.7% (65/121), which was higher in the HAM/TSP group (80.0%; adjusted PR 1.89; 95% CI 1.23–2.90) when compared with non-infected individuals (44.9%). Sexual dysfunction was found in 54.4% of the HTLV-1–infected asymptomatic women (PR 1.21; 95% CI 0.82–1.79). Sexual dysfunction was associated with income lower than 1 minimal wage (∼US 300, October 2017) and number of previous birthday. Conclusion: The obtained results indicate that sexual dysfunction is associated with HAM/TSP in women infected with HTLV-1 of reproductive age.